ANALISIS PENGARUH MODAL KERJA DAN TENAGA KERJA TERHADAP PENDAPATAN PETANI TAMBAK GARAM DI KECAMATAN KALIANGET KABUPATEN SUMENEP (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
This study aims to determine whether there is an effect of working capital and labor on the income of salt pond farmers in Kalianget District, Sumenep Regency. This study uses quantitative methods with questionnaires, documentation, and observation data collection techniques. The method used is multiple linear regression analysis, analysis of determination (R2), and hypothesis testing. This data collection technique was carried out by distributing questionnaires to 78 respondents, namely smallholder salt pond farmers in Kalianget District, Sumenep Regency. The results of this study prove that partially working capital and labor have a significant effect on the income of smallholder salt pond farmers in Kalianget District, Sumenep Regency. Simultaneously working capital and labor have a significant effect on the income of salt farmers in Kalianget District, Sumenep Regency.